2018
DOI: 10.4067/s0718-221x2018005004101
|View full text |Cite
|
Sign up to set email alerts
|

Using artificial neural networks in estimating wood resistance

Abstract: The purpose of this research was to evaluate the potential of Artificial Neural Networks in estimating the properties of wood resistance. In order to do so, a hybrid of eucalyptus (Eucalyptus urograndis) planted in the Northern Region of the State of Mato Grosso was selected and ten trees were collected. Then, four samples of each tree were removed, totaling 40 samples, which were later subjected to non-destructive testing of apparent density, ultrasonic wave propagation velocity, dynamic modulus of elasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…21,26,27,75,76 In addition, the ANNs and remotely sensed data combined can provide higher modeling precision in forest sites than the regression models, as they are able to assimilate a high complexity and variety of vegetation, environment, and climatic aspects. 21,24 Although developing prediction models using ANNs is a high-complexity task that requires skilled labor and high computational capacity for training them, the ANN has achieved higher estimate precisions when modeling complex relationships among different variables. 22,75,77 More specifically, in this study, it was required approximately 50 working hours of one highly skilled person to train, validate, and apply the ANN model using our datasets and a classical personal computer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,26,27,75,76 In addition, the ANNs and remotely sensed data combined can provide higher modeling precision in forest sites than the regression models, as they are able to assimilate a high complexity and variety of vegetation, environment, and climatic aspects. 21,24 Although developing prediction models using ANNs is a high-complexity task that requires skilled labor and high computational capacity for training them, the ANN has achieved higher estimate precisions when modeling complex relationships among different variables. 22,75,77 More specifically, in this study, it was required approximately 50 working hours of one highly skilled person to train, validate, and apply the ANN model using our datasets and a classical personal computer.…”
Section: Discussionmentioning
confidence: 99%
“…The adjustment and training of the artificial neural networks (ANNs) to estimate the AGB were carried out on the Statistica software version, 26,43 aiming to achieve the lowest prediction error rate. 24 The ANNs were trained based on supervised approach by defining the input and output variables and using the multilayer perceptron (MLP) architecture type, as applied by Ref. 23.…”
Section: Training the Artificial Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, decay assessment using NDTs was researched in Branco et al (2017) and Sousa et al (2017) where, through the use of damage maps, it was possible to pinpoint regions of the structure and even of segments of the elements which had different levels of decay and their probable sources. To analyse the variation of timber properties along one element, due to different levels of conservation, scale and natural variability of wood, some of the more recent studies tried different prediction models, such as and Sousa et al (2018) with hierarchical models and probabilistic models using Bayesian methods, García-Iruela, et al (2016) and Miguel, et al (2018) with artificial neural networks. Furthermore, some research already showed the promising results using combination of different NDTs, such as Cavalli and Togni (2013) found that using pin penetration depth and stress wave velocity, the prediction of bending modulus is high, and Vega, et al (2012) also found the highest predictability of bending modulus by the combination of vibration wave velocity, density and sample length.…”
Section: Introductionmentioning
confidence: 99%
“…There are a growing number of papers in the field of wood science employing artificial neural network (ANN), such as predicting physical and mechanical properties in wood and wood composites (Fernandez et al, 2008;Fernandez et al, 2012;Melo and Miguel, 2016;Ilkucar et al, 2018;Miguel et al, 2018), calculating wood thermal conductivity (Avradimis and Iliadis, 2005;Xu et al, 2007), classifying wood defects (Marcano-Cedeño et al, 2009;Shahnorbanun et al, 2010;Qayyum et al, 2016), optimizing of bonding strength of the various wood products (Cook and Chiu, 1997;Tiryaki et al, 2014) and analysing of moisture in wood (Zhang et al, 2006;Esteban et al, 2010;Özşahin, 2012).…”
Section: Introductionmentioning
confidence: 99%